2021
DOI: 10.1371/journal.pgen.1009295
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulates synaptic subcellular specificity mediated by inhibitory glutamate signaling

Abstract: Environmental factors such as temperature affect neuronal activity and development. However, it remains unknown whether and how they affect synaptic subcellular specificity. Here, using the nematode Caenorhabditis elegans AIY interneurons as a model, we found that high cultivation temperature robustly induces defects in synaptic subcellular specificity through glutamatergic neurotransmission. Furthermore, we determined that the functional glutamate is mainly released by the ASH sensory neurons and sensed by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 128 publications
1
9
0
Order By: Relevance
“…48 Environmental factors like temperature can regulate the neuronal activity of AIY interneurons through inhibitory glutamate signaling, which influences the subcellular synaptic specificity in C. elegans. 49 In this study, we found that OGT-1 and DAF-2 are required for regular AIY neuronal activity, which was consistent with the findings of previous studies, where it was reported that nutrient metabolism is essential for regulating neuronal activity. 50 However, the precise mechanisms through which OGT-1 and DAF-2 regulate neuronal activity and subsequently affect synaptic assembly need to be further elucidated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…48 Environmental factors like temperature can regulate the neuronal activity of AIY interneurons through inhibitory glutamate signaling, which influences the subcellular synaptic specificity in C. elegans. 49 In this study, we found that OGT-1 and DAF-2 are required for regular AIY neuronal activity, which was consistent with the findings of previous studies, where it was reported that nutrient metabolism is essential for regulating neuronal activity. 50 However, the precise mechanisms through which OGT-1 and DAF-2 regulate neuronal activity and subsequently affect synaptic assembly need to be further elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…For example, when activated by aversive odorants, AMsh glia can release GABA to suppress the neuronal activity of ASH sensory neurons and regulate the olfactory adaptation in C. elegans 48 . Environmental factors like temperature can regulate the neuronal activity of AIY interneurons through inhibitory glutamate signaling, which influences the subcellular synaptic specificity in C. elegans 49 . In this study, we found that OGT‐1 and DAF‐2 are required for regular AIY neuronal activity, which was consistent with the findings of previous studies, where it was reported that nutrient metabolism is essential for regulating neuronal activity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…glc-4 is expressed in intestine, anal depressor muscle, head mesodermal cells, nerve ring, head, and tail neurons, and the mutants show hypersensitivity to ivermectin and hyper reversal behavior ( Pellegrino, 2003 ). Wang et al (2021) reported colocalization of GLC-3 and GLC-4 in AIY interneurons and identified their role in regulating temperature-dependent neurological behavior. Unlike previously expressed GluCl subunits, GLC-4A failed to assemble into a functional homomeric GluCl channel but forms a heteromeric channel with AVR-14B altering its pharmacological properties with decreased current response to glutamate and IVM ( Pellegrino, 2003 ).…”
Section: Ligand-gated Ion Channelsmentioning
confidence: 99%
“…To determine whether Wnt/ nlp‐40/aex‐2 regulates AIY activity, we recorded AIY calcium signaling using GCaMP6, a genetically encoded calcium indicator (Fig 5A and A') (Luo et al , 2014). In wild‐type animals, AIY spontaneously fires about six times per minute (Wang et al , 2021). In cfz‐2(ok1201) , nlp‐40(tm4085) or aex‐2(sa3) mutants, although the firing amplitude was not affected (Fig 5B and D), the frequency was significantly reduced (Fig 5B and C), and the activity defects were rescued by expressing the corresponding wild‐type transgene (Fig 5B and C).…”
Section: Resultsmentioning
confidence: 99%
“…The invertebrate neural circuits were initially thought to be genetically hardwired (Jin et al , 1999; Gally & Bessereau, 2003; Hiesinger et al , 2006; Klassen & Shen, 2007), although neural activity can regulate the remodeling or plasticity (Zhao & Nonet, 2000; Sachse et al , 2007; Tessier & Broadie, 2009; Thompson‐Peer et al , 2012; Hart & Hobert, 2018; Cuentas‐Condori et al , 2019). However, recent studies have shown that neuronal activity during embryogenesis regulates neuronal differentiation (Horowitz et al , 2019), presynaptic subcellular specificity (Wang et al , 2021) in C. elegans , indicating the important role of experience‐independent activity in circuit development. In vertebrates, it is well known that neural activity regulates synaptic formation and plasticity (Hooks & Chen, 2020; Pan & Monje, 2020).…”
Section: Discussionmentioning
confidence: 99%